High Molecular Weight Adiponectin and Incident Ischemic Stroke in Postmenopausal Women: A Women’s Health Initiative Study - Ogorodnikova, Alexandra D. (2010)
BACKGROUND AND PURPOSE: While low levels of adiponectin are associated with coronary heart disease and cardiovascular disease (CVD) risk factors, it is unclear whether adiponectin levels are related to the risk of developing ischemic stroke. METHODS: We examined the relationship between baseline high molecular weight (HMW) adiponectin levels and incident ischemic stroke in postmenopausal women, using data and specimens from the Hormones and Biomarkers Predicting Stroke Study, a case-control study nested within the Women’s Health Initiative Observational Study. Included were 855 incident ischemic stroke cases and 855 controls, matched for age, race-ethnicity, date of entry into the cohort, and follow-up time. Odds ratios of incident ischemic stroke associated with baseline HMW adiponectin levels were calculated using conditional logistic regression modeling, adjusting for body mass index (BMI), type 2 diabetes, hypertension, smoking, LDL-C, HDL-C, physical activity, C-reactive protein, and aspirin use. RESULTS: Lower levels of HMW adiponectin were significantly associated with type 2 diabetes, hypertension, higher BMI, waist, glucose, and insulin levels, and lower HDL-C levels. The distribution of incident stroke cases by HMW adiponectin quartiles was 49.9%, 50.5%, 50.7%, and 48.9%, respectively (p =0.96). Multivariable-adjusted odds ratios of stroke associated with the top three quartiles of HMW adiponectin versus the first quartile were 0.99 (95%CI 0.71 to 1.37), 1.37 (0.99 to 1.91), and 1.25 (0.88 to 1.79), respectively (p-trend =0.14). CONCLUSION: Despite moderate associations between HMW adiponectin and CVD risk factors, we found no evidence of an association between HMW adiponectin levels and incident ischemic stroke in these postmenopausal women.